Glucose sensing in pancreatic islet beta cells: the key role of glucokinase and the glycolytic intermediates. - German, M S (1993)
The beta cells of the pancreatic islets of Langerhans respond to changes in glucose concentration by varying the rate of insulin synthesis and secretion. Beta cells sense glucose concentration by the levels of the products of glucose catabolism. Distinctive beta-cell proteins glucose transporter 2 and glucokinase catalyze the first two steps in beta-cell glucose catabolism. To test whether either protein controls the sensitivity of the beta cell to glucose by controlling the rate of glucose catabolism, we used gene-transfer techniques to express the isoenzymes glucose transporter 1 and hexokinase I in beta cells and measured the response to glucose of the insulin gene promoter. Cells expressing glucose transporter 1 do not differ significantly from control cells, but in cells expressing hexokinase I, insulin promoter activity increases, reaches a maximum by 1 mM glucose, and does not respond to changes in glucose concentration within the physiologic range. We conclude that glucokinase catalyzes the rate-limiting step of glucose catabolism in beta cells and, therefore, acts as the glucose sensor. Pyruvate, the end product of anaerobic glycolysis, is readily oxidized by mitochondria in normal beta cells but cannot substitute for glucose as a stimulator of insulin synthesis and secretion. We found that pyruvate can stimulate the insulin promoter in cells expressing the bacterial gluconeogenic enzyme phosphoenolpyruvate carboxykinase, which allows the conversion of pyruvate to phosphoenolpyruvate and the earlier intermediates of glycolysis. We conclude that the intermediates of anaerobic glycolysis between fructose 1,6-diphosphate and phosphoenolpyruvate are essential for beta-cell glucose sensing.